EMBEDDING ACADEMIC LITERACY WITHIN INCLUSIVE PEDAGOGY IN SPECIAL EDUCATION TEACHER EDUCATION: A QUALITATIVE STUDY IN AN INDONESIAN UNIVERSITY - Sri Wahyudi; Nur Hidayat Cahyono (CV. TOTUS TUUS, 2026)
Inclusive teaching in higher education is increasingly required to accommodate diverse student profiles, particularly in special education teacher education where candidates must internalize and model inclusive values. However, academic literacy (e.g., reading scholarly texts, constructing evidence-based arguments, and writing systematically) is often uneven among students and is frequently treated as a separate skill rather than integrated into inclusive pedagogy. This study aimed to analyze how inclusive learning strategies are integrated with academic literacy strengthening in a special education course and to examine their implications for learning processes and outcomes. Using a qualitative descriptive design, data were collected through classroom observations, in-depth semi-structured interviews with lecturers and students, and document analysis of syllabi, lesson plans, learning materials, and student assignments. Data were analyzed through iterative reduction, display, and conclusion drawing, supported by method and source triangulation. Findings indicate that integrating inclusive pedagogy with explicit academic literacy practices increased student engagement, improved conceptual understanding, and strengthened critical and reflective thinking. Flexible and collaborative learning designs expanded equitable participation across students with varied backgrounds and abilities, while literacy-based tasks enhanced students’ capacity to interpret scholarly sources and communicate ideas more rigorously. The study concludes that this integration is both feasible and pedagogically valuable for improving instructional quality and professional readiness in special education teacher preparation. Implications include the need for curriculum-level alignment of inclusive strategies with structured literacy scaffolds and formative feedback. Future research should test the model across institutions using mixed methods and longitudinal designs to examine sustained academic and professional impacts.